Lapacho Sorpresa Rosa INTA: Proyecto de modelo de transferencia - Facciuto, Gabriela Rosa; Bugallo, Veronica Lucia; Pidal, Bárbara; Sanchez, Marcela Ines; Soto, Maria Silvina (Instituto Misionero de Biodiversidad, 2023)
Poster